The Needs of Military-Connected Students within the North Carolina Public School System - Lupton, Meagan E (East Carolina University, 2016)
The present study assessed how the mental health needs of military-connected students are addressed within public schools in the state of North Carolina, particularly how aware and comfortable school staff are regarding issues common to military-connected students and what trainings have been offered to them. Participants were 71 school personnel (i.e. principals, school counselors, and teachers) from Camden County, Craven County, Cumberland County, and Richmond County schools. These participants also represented schools that serve families from all five branches of the armed forces (i.e. Air Force, Army, Coast Guard, Marine Corps, and Navy). The ability of these personnel to identify issues highly correlated with military-connected students was assessed via an eighteen item electronic survey. This survey also addressed which related training programs participants have attended, as well as which related services schools currently have in place. Findings indicated that more than half of participants were unable to identify the needs common to military-connected students. Also, more than half (80.00%) of participants had not received any training related to the needs of military-connected students. Those participants who had received formal training perceived themselves as more confident in their abilities to serve this population of students than did their colleagues who had not. Funding for those training programs was predominantly financed by a branch of service or a military-connected organization (52.38%), followed by individual school districts (38.10%). Lastly, findings indicated that many schools are using a related service (i.e. welcome packet, buddy system, support groups) designed to assist their military-connected student population.
Keywords: Students; Children of military personnel--Mental health--North Carolina; Public schools--Employees--Training of--North Carolina.